2023
DOI: 10.1021/acs.est.3c04770
|View full text |Cite
|
Sign up to set email alerts
|

Cloth–Air Partitioning of Neutral Per- and Polyfluoroalkyl Substances (PFAS) in North Carolina Homes during the Indoor PFAS Assessment (IPA) Campaign

Clara M. A. Eichler,
Naomi Y. Chang,
Elaine A. Cohen Hubal
et al.

Abstract: Partitioning of per- and polyfluoroalkyl substances (PFAS) to indoor materials, including clothing, may prolong the residence time of PFAS indoors and contribute to exposure. During the Indoor PFAS Assessment (IPA) Campaign, we measured concentrations of nine neutral PFAS in air and cotton cloth in 11 homes in North Carolina, for up to 9 months. Fluorotelomer alcohols (i.e., 6:2 FTOH, 8:2 FTOH, and 10:2 FTOH) are the dominant target species in indoor air, with concentrations ranging from 1.8 to 49 ng m– 3, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 82 publications
(186 reference statements)
0
0
0
Order By: Relevance
“…Another study reported much higher concentrations of 6:2 FTOH (10000−600000 pg/m 3 ) and 8:2 FTOH (2000−160000 pg/m 3 ) in kindergartens in California . 6:2 FTOH, 8:2 FTOH, and 10:2 FTOH were the predominant PFAS species in indoor air environments, presenting concentration ranges of 1800−49000, 1200−5300, and 210−5700 pg/m 3 , respectively, in North Carolina . FTOH concentrations in offices in Boston ranged from not detected to 13000 pg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported much higher concentrations of 6:2 FTOH (10000−600000 pg/m 3 ) and 8:2 FTOH (2000−160000 pg/m 3 ) in kindergartens in California . 6:2 FTOH, 8:2 FTOH, and 10:2 FTOH were the predominant PFAS species in indoor air environments, presenting concentration ranges of 1800−49000, 1200−5300, and 210−5700 pg/m 3 , respectively, in North Carolina . FTOH concentrations in offices in Boston ranged from not detected to 13000 pg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Whereas diet is thought to be an important source of PFAS exposure, contribution from other sources such as inhalation of indoor air is not known . Humans spend most of their time indoors, and volatile PFAS precursors such as FTOHs are often found at elevated concentrations in indoor air. , Inhalation of PFAS through indoor air is an important exposure pathway for children . Some studies have reported the occurrence of FTOHs in indoor and outdoor air, but there is limited research on concurrent analysis of emerging neutral (nPFAS) and ionic PFAS (iPFAS) present in indoor air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, Eichler et al measured total gas-phase FTOH in eleven homes from North Carolina, USA, with concentrations ranging from 2.0 to 94 ng m −3 . 22 Despite the ubiquity and implications of PFAS to human and ecological health, progress in understanding the sources, transformations, lifetimes, and fates of PFAS in indoor and outdoor air is hampered by the long averaging times (hours to months) currently required for sampling neutral and ionic PFAS in air. 22–30…”
Section: Introductionmentioning
confidence: 99%
“…To address the need for real-time quantitative measurements of gas-phase PFAS, we describe and demonstrate the viability of a simple and cost-effective Calibration Apparatus for Manual Injection of Liquid Standards (CAMILS), utilizing the same seven compounds as Riedel et al 36 as well as three additional compounds not previously measured by I-HR-ToF-CIMS but which are relevant to indoor or outdoor air ( i.e. , one perfluorooctane sulfonamide (EtFOSA), 15,22,38 one fluorotelomer diol (FTdiOH), 39 and one fluorinated ether (E2)). 40 External calibration of I-HR-ToF-CIMS with the CAMILS allows for reproducible, real-time quantification of gas-phase PFAS, offering greatly enhanced temporal resolution as compared to offline methods.…”
Section: Introductionmentioning
confidence: 99%